ANALISIS PERBANDINGAN WAKTU PADA PEKERJAAN REVETMENT ANTARA METODE PASANGAN BATU DENGAN METODE L-GUTTER - Bagus Tri Winarso; Edy Purwanto (JURNAL ILMIAH NUSANTARA, 2024)
Floods are an annual problem and have a major impact on the condition of society both socially, economically and environmentally (Sholikha et al., 2022). Floods that occur in the Ledeng River, in addition to causing erosion of river banks and causing damage to the place where the erosion occurs, also damage the areas that receive the results of the erosion. As an effort to deal with this, a Revetment is built. The purpose of this study was to determine the difference in the time of Revetment work using stone masonry with precast L-Gutter. The research method used was direct observation in the field. Observations were carried out twice, including observations of the time of Revetment work using river stone masonry and observations of the time of Revetment work with precast L-Gutter. The results of the study showed that the construction time for the stone masonry method was 11 days longer than the L-Gutter method.